Senegal : Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report, 2010)
It is vital to achieve both high levels of sustained, long lasting growth and better income distribution through the Accelerated Growth Strategy in Senegal. In terms of macroeconomic performance, the annual average growth rate dropped owing to exogenous shocks and low productivity in the agricultural subsector. The economy is confronted by infrastructure deficits, a weak industrial fabric, and a continuing shortage of private investment. The objectives of economic emergence and achievement of all the Millennium Development Goals (MDGs) call for implementation of an integrated strategy focused on the challenges.